Taxpayer Compliance: The Role of Taxation Digitalization System and Technology Acceptance Model (TAM) with Internet Understanding as a Mediating Variable - Dian Sulistyorini Wulandari; Sunita Dasman (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the correlation of the technology acceptance model and digital taxation on taxpayer compliance, with Internet understanding as a mediating variable. The method used in this study is multiple regression analysis with moderating calculations using the interaction method. Process data using the Smart PLS application. The sample in this study consisted of 62 individual taxpayers who had NPWP registered at KPP Pratama Cikarang Selatan. The results of this study indicate that, first, the tax digitization system has a positive but insignificant effect on taxpayer compliance. Second, the Tax Digitization System positively and significantly influences the Internet Understanding of Mediation Variables. Third, the technology acceptance model (TAM) positively and significantly influences taxpayer compliance. Fourth, the Technology Acceptance Model (TAM) has a negative and not significant effect on the Internet Understanding of Mediation variables. Fifth, Internet comprehension has a positive and insignificant influence on taxpayer compliance.